FMD RAPID DIAGNOSTIC TEST IN ACEH INDONESIA: A TECHNICAL NOTE - AK, M. Daud; Abrar, Mahdi; Ferasyi, Teuku Reza (Universitas Syiah Kuala, 2024)
This study aims to offer a detailed technical note thorough examination of the pioneering and effectiveness of FMD immediate diagnostic tests in Aceh, Indonesia. We discuss the key components of these tests, including their sensitivity, specificity, and practicality in resource-limited settings. Furthermore, we explore the challenges and opportunities associated with adopting these tests locally and highlight their potential impact on FMD surveillance and control efforts. The findings presented in this technical note contribute to the ongoing efforts to combat FMD in Aceh, providing valuable insights into using rapid diagnostic tests as a vital tool in disease management strategies. The results showed that the FMD rapid diagnostic test kit has limited sensitivity in detecting early clinical signs of FMD in cattle in Aceh. Therefore, Further examination with laboratory molecular detection methods is needed.